2011
DOI: 10.1007/s11356-011-0491-7
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of a sulphonated azo dye Green HE4B by Glandularia pulchella (Sweet) Tronc. (Moss Verbena)

Abstract: This study explored the phytoremediation ability of G. pulchella (Sweet) Tronc. in degrading Green HE4B into non-toxic metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 20 publications
5
29
0
Order By: Relevance
“…Riboflavin reductase was absent in the control set, but its activity was significantly increased during the biodegradation of DR54, suggesting that this particular enzyme was instantly synthesized upon exposure to DR54. The positive role and action of these oxidative and reductive enzymes in the biodegradation of various recalcitrant textile dyes such as Green HE4B (12), Remazol red, Rubine GFL (21), Acid Violet 19, Amaranth (20,37), and mixtures of dyes (28) have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Riboflavin reductase was absent in the control set, but its activity was significantly increased during the biodegradation of DR54, suggesting that this particular enzyme was instantly synthesized upon exposure to DR54. The positive role and action of these oxidative and reductive enzymes in the biodegradation of various recalcitrant textile dyes such as Green HE4B (12), Remazol red, Rubine GFL (21), Acid Violet 19, Amaranth (20,37), and mixtures of dyes (28) have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Methanol was used as mobile phase (flow rate of 1 mL min À1 ) and products were detected using UV detector at 470 and 260 nm. The FTIR (Spectrum One, PerkineElmer) analysis of control dye and extracted metabolites was carried out according to the protocol reported by Kabra et al (12). Briefly, the FTIR analysis was conducted in the mid IR region of 400e4000 cm À1 with 8 scan speed.…”
Section: Determination Of Enzyme Activitiesmentioning
confidence: 99%
“…These plants exhibited constantly the same removal efficiency against the dye during four repeated runs (Vafaei et al, 2013b;Khataee et al, 2013;Torbati et al, 2015). The hairy roots of G. pulchella also showed effective absorption of different textile dyes provided (Kabra et al, 2011). Hence it is evident from the above mentioned facts that biosorption phenomenon within different plant species is vital in sequestration, accumulation and subsequent metabolism of toxic dyes.…”
Section: Sorption and Speciation Of Dye Stuffs Within Plant Tissuesmentioning
confidence: 74%
“…Studies have also revealed that plant species are genetically adapting over the passage of time to survive and grow on highly polluted substrates in order to metabolize or detoxify the contaminants to alleviate environmental stresses. Thus suggesting that plants as autotrophic and natural solar-driven bioreactors can effectively be utilized for remediation purposes (Campos et al, 2008;Sureshvarr et al, 2010;Kabra et al, 2011).…”
Section: Phytoremediationmentioning
confidence: 99%
“…), which are used for phytoremediation, also carry Ralstonia as an endophyte besides Acinetobacter , Pseudomonas , and Xanthomonas . Ralstonia is also an endophyte of Anthurium , Brassica juncia , Geranium , Gerbera , Heliconia , Mimosa , Salvia , sunflower, tobacco, Verbena , and Zinnia , which are also used for phytoremediation of sites contaminated with inorganic and organic pollutants (Ikeura et al, ; Kabra, Khandare, Kurade, & Govindwar, ; Liu, Xin, & Zhou, ; Madera‐Parra, Peña‐Salamanca, Pena, Rousseau, & Lens, ; Mahdieh, Yazdani, & Mahdieh, ). For example, R. eutropha was effective in combination with sunflower ( Helianthus ) for phytoremediation of sites contaminated with Cd and Zn (Marques, Moreira, Franco, Rangel, & Castro, ), with maize for phytoremediation of sites contaminated with Cd (Moreira, Marques, Franco, Rangel, & Castro, ), and with Juncus acutus for biotransformation of Cr(VI) (Dimitroula et al, ).…”
Section: Role Of Filamentous Phages In the Monitoring Bacterial Inocumentioning
confidence: 99%